Taxonomic and systematic revisions to the North American Nimravidae (Mammalia, Carnivora) - Barrett, Paul Z. (PeerJ, 2016)
The Nimravidae is a family of extinct carnivores commonly referred to as “false saber-tooth cats.” Since their initial discovery, they have prompted difficulty in taxonomic assignments and number of valid species. Past revisions have only examined a handful of genera, while recent advances in cladistic and morphometric analyses have granted us additional avenues to answering questions regarding our understanding of valid nimravid taxa and their phylogenetic relationships. To resolve issues of specific validity, the phylogenetic species concept (PSC) was utilized to maintain consistency in diagnosing valid species, while simultaneously employing character and linear morphometric analyses for confirming the validity of taxa. Determined valid species and taxonomically informative characters were then employed in two differential cladistic analyses to create competing hypotheses of interspecific relationships. The results suggest the validity of twelve species and six monophyletic genera. The first in depth reviews of Pogonodon and Dinictis returned two valid species (P. platycopis, P. davisi) for the former, while only one for the latter (D. felina). The taxonomic validity of Nanosmilus is upheld. Two main clades with substantial support were returned for all cladistic analyses, the Hoplophoneini and Nimravini, with ambiguous positions relative to these main clades for the European taxa: Eofelis, Dinailurictis bonali, and Quercylurus major; and the North American taxa Dinictis and Pogonodon. Eusmilus is determined to represent a non-valid genus for North American taxa, suggesting non-validity for Old World nimravid species as well. Finally, Hoplophoneus mentalis is found to be a junior synonym of Hoplophoneus primaevus, while the validity of Hoplophoneus oharrai is reinstated.